Hyperprogression disease induced by Sintilimab combined with Oxaliplatin and S-1 after surgery: a case report and literature review - Li, Yaoqi; Wang, You; Shen, Rui; Liu, Weijun; Zhu, Chenglou (Frontiers in Oncology, 2025)
ObjectiveTo investigate the risk factors, underlying mechanisms, and preventive strategies associated with hyperprogressive disease (HPD) induced by immunotherapy.MethodsWe analyzed the clinical data of a patient who developed HPD following palliative gastrectomy and received a combination therapy of Sintilimab, S-1 (tegafur, gimeracil, and oteracil potassium), and Oxaliplatin (SOX). Additionally, a literature review on tumor immunotherapy was conducted to further explore the risk factors and mechanisms of HPD.ResultsIn this case, the development of HPD was associated with a high postoperative tumor burden, elevated PD-1 expression, and aberrant activation of signaling pathways mediated by EGFR, MET, and FGFR1 amplifications. In addition, a TP53 p.F270V mutation led to inactivation of tumor suppressor function.ConclusionAlthough immune checkpoint inhibitors (ICIs) have demonstrated significant efficacy in cancer treatment, HPD induced by ICIs can drastically shorten patients’ OS, warranting cautious use in populations with high-risk factors. Effective prevention of HPD involves screening for risk factors, monitoring predictive biomarkers such as circulating-free DNA (cfDNA) via liquid biopsy, and identifying high-risk populations through gene mutation analysis.